2020
DOI: 10.3390/pharmacy8010038
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Medication Adherence Using M-Health: A Study from Veterinary Medicine

Abstract: Background: Pharmacy practice includes the handling of human and animal medication. Amongst veterinary pharmaceutical treatments, the management of Canine Atopic Dermatitis (CAD), a chronic skin condition affecting 10%–15% of the canine population, is complex and demanding. Medication regimens are tailored to each animal and their owner or caregiver. The purpose of this study was to assess the impact of a mobile health (m-health) application (Petable®) to support the medication adherence in CAD treatment and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Therapeutic adherence was measured using a published tool ( Medida de Adesão aos Tratamentos or the MAT questionnaire) 35 . This tool was validated in 2001 for people 35 and adapted into a veterinary context by direct changes in the wording (MATv) 6 . All clients answered the MATv at D56, and, as the validation paper instructs, any owner with a score equal or superior to the median value was considered successfully adherent 35…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therapeutic adherence was measured using a published tool ( Medida de Adesão aos Tratamentos or the MAT questionnaire) 35 . This tool was validated in 2001 for people 35 and adapted into a veterinary context by direct changes in the wording (MATv) 6 . All clients answered the MATv at D56, and, as the validation paper instructs, any owner with a score equal or superior to the median value was considered successfully adherent 35…”
Section: Methodsmentioning
confidence: 99%
“…A study performed in 2020 also evaluated the adherence of pet owners to a therapeutic plan in a number of dogs with cAD. 6 Compliance was measured using a mobile health application (Petable) in addition to the MATv tool, used in our study. In that study, the MATv results showed that only 60% of the owners adhered to the treatment plan.…”
Section: Ta B L E 2 Contingency Table Showing Fisher's Exact Test Res...mentioning
confidence: 99%
See 2 more Smart Citations
“…Many interventions for increasing adherence have been tested, and 771 intervention trials suggest that healthcare providers should focus the intervention content more on behavioral strategies than on cognitive strategies designed to change knowledge levels and beliefs (Conn & Ruppar, 2017). Some studies on adherence have been conducted in companion animals (Lavan et al, 2020; Ribas et al, 2020) but not in production animals.…”
Section: Introductionmentioning
confidence: 99%